2017
DOI: 10.1002/ase.1704
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stereoscopic imagery and motion on anatomical structure recognition and visual attention performance

Abstract: Gross anatomy is located in a three-dimensional space. Visualizing aspects of structures in gross anatomy education should aim to provide information that best resembles their original spatial proportions. Stereoscopic three-dimensional imagery might offer possibilities to implement this aim, though some research has revealed potential impairments that may result from observing stereoscopic visualizations, such as discomfort. However, possible impairments of working memory such as decreased visual attention pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 57 publications
0
23
1
1
Order By: Relevance
“…The superiority of learning with stereoscopic vision has been demonstrated in one previous study, although they showed that this was confined to static presentations, where the participant could not manipulate the representation. In the present study, participants were at liberty to move both PM and 3DVT models at will in any direction, and the advantage of stereoscopic vision was still present.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The superiority of learning with stereoscopic vision has been demonstrated in one previous study, although they showed that this was confined to static presentations, where the participant could not manipulate the representation. In the present study, participants were at liberty to move both PM and 3DVT models at will in any direction, and the advantage of stereoscopic vision was still present.…”
Section: Discussionmentioning
confidence: 80%
“…Remmele compared stereoscopic to non‐stereoscopic presentations on a computer screen (using polarising glasses) and found a large advantage for stereo, when the presentation was static (ES = 1.11). This leaves unanswered how a PM would compare to a 3DVT dynamic but non‐stereoscopic presentation, because, as Remmele pointed out, a dynamic presentation contains many of the visual cues to the third dimension. Moreover, dynamic movement is a component of both PM and 3DVT presentations.…”
Section: Goalsmentioning
confidence: 99%
“…Wainman et al (2018) did show that the removal of stereopsis during the learning task significantly decreased performance on the PM but not the 2D VR model which indicates both that stereopsis is a critical determinant of performance in anatomy learning and that stereopsis is not present in 2D VR. Previous studies have also shown that a critical element for a modality to yield a learning advantage over a simple static 2D display is the provision of true stereopsis (Cui et al, 2017;Hackett and Proctor, 2018;Remmele et al, 2018;Wainman et al, 2018). A PM selfevidently incorporates 3D; however, it is less clear whether MR and VR technologies do.…”
Section: Discussionmentioning
confidence: 99%
“…A final study that systematically explored two causal features was conducted by Remmele et al (2018) who taught anatomy of the ear using purpose-built software and hardware, systematically varying stereoscopic or non-stereoscopic presentation, and dynamic under user control or static presentation. They found a large main effect of stereoscopic presentation (consistent with Cui et al, 2017, Hackett and Proctor, 2018and Wainman et al, 2018, no effect of dynamic presentation (consistent with observations from Garg et al, 1999 andKhot et al, 2013), and a small interaction (Remmele et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Three‐dimensional representations of the human body have been used successfully as additional tools to teach anatomy, e.g., Zygote Body, and were found to be cost‐effective and welcomed by students (Estai and Bunt, 2016; Losco et al, 2016; Preim and Saalfeld, 2018). The introduction of virtual reality (VR) in science, offered a learning alternative that produced a sensation of depth and movement similar to that perceived in the real world (Steuer, 1992; Wainman et al, 2018); this immersive experience, capable of enhancing the appreciation of spatial relations between structures was successfully applied to anatomy (Remmele et al, 2018). As a training tool, VR was found to improve SA, particularly in women, closing the gender gap in post‐training SA scores (Dünser et al, 2006), despite temporary adverse effects, e.g.…”
Section: Introductionmentioning
confidence: 99%